2023
DOI: 10.3390/met13020226
|View full text |Cite
|
Sign up to set email alerts
|

Study of Tensile Deformation and Damage Law in Undermatching X80 Pipeline Steel Welded Joints

Abstract: This study used a digital imaging technique (DIC) to obtain the strain distribution at various locations in undermatching X80 pipe girth-weld joints under uniaxial tensile loading. In addition, the microstructure characteristics and deformation patterns in different regions were analyzed by scanning electron microscopy (SEM). The results showed that there was strain heterogeneity between the various regions of the welded joint. Strain concentration existed only in the 12.8 mm base metal heat-affected zone (HAZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The results show that the carrying capacity of the girth weld is greatly reduced due to shearing action. Previous studies [17] clarified the strain law, deformation behavior and microstructure characteristics of undermatched X80 welded joints in practical applications. The pattern of strain concentration in the weld region varies in different tensile stages, leading to severe damage and final fracture of the weld.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the carrying capacity of the girth weld is greatly reduced due to shearing action. Previous studies [17] clarified the strain law, deformation behavior and microstructure characteristics of undermatched X80 welded joints in practical applications. The pattern of strain concentration in the weld region varies in different tensile stages, leading to severe damage and final fracture of the weld.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that even in the case of a ductile structural steel (S235), fracture can occur at a relatively low stress level. Another study with DIC was performed to obtain the strain distribution in undermatching X80 pipe weld joints under uniaxial tensile loading, [ 18 ]. The results showed that the maximum strain was in the WM.…”
Section: Introductionmentioning
confidence: 99%
“…Pipeline steel is generally required to have high plasticity and toughness. Under large strain loads, pipeline steel undergoes ductile fracture, accompanied by the nucleation, growth and coalescence of void at the microscopic level [8,9,12]. At low temperatures, brittle fracture of the pipeline steel may occur due to a decrease in toughness [10,13].…”
Section: Introductionmentioning
confidence: 99%